From GOCE to NGGM: Automatic Control Breakthroughs for European future Gravity Missions. Issue 1 (July 2017) - Bacchetta, A.; Colangelo, L.; Canuto, E.; Dionisio, S.; Massotti, L.; Novara, C.; Parisch, M.; Silvestrin, P.
Abstract: After the successful European gravity mission GOCE (Gravity field and steady-state Ocean Circulation Explorer), which provided an unprecedented high resolution static global map of the Earth's gravity field, the European Space Agency has proposed several preparatory studies for a Next Generation Gravity Mission (NGGM). The NGGM mission objective aims at measuring the temporal variations of the Earth gravity field over a long time span with an unprecedented level of accuracy, both in spatial and temporal resolution. The GOCE technological heritage is leveraged as starting point while defining the NGGM future mission concept. Nonetheless, to accomplish its challenging scientific objective, the NGGM mission concept envisages a wide range of innovations, with respect to the past or flying missions, both on technological and automatic control side. Thus, this paper focuses on the guidance, navigation and control design evolution for the European gravity missions, from GOCE to NGGM. After recalling the GOCE GNC main design concepts, the paper will describe the most important innovation required by NGGM. Indeed, such a future concept will consist of a two-satellite long-distance loose formation, where each satellite is controlled independently to be drag-free, GOCE-like. The satellite-to-satellite distance variations, encoding gravity anomalies, will be then measured by laser heterodyne interferometry for inter-satellite ranging at 20 nm resolution, or better. Hence, an orbit and formation control is now required to counteract bias and drift of the residual drag-free accelerations, in order to reach a bounded orbit/formation long-term stability. Finally, GOCE control flight results as well as NGGM simulated results, via a high-fidelity simulator, will be provided. These results highlight the GOCE GNC in-flight achievements as well as the NGGM concept validity, showing that the expected control performances are in agreement with the consolidated mission requirements, all over the 10-year mission.